Soluble vascular cell adhesion molecule-1 levels and severity of dengue hemorrhagic fever in children - Nolitriani Nolitriani; Rinang Mariko; Mayetti Mayetti (Paediatrica Indonesiana, 2021)
Background The clinical manifestations of dengue infection vary widely, ranging from asymptomatic to severe forms that can cause death. In severe infections, the expression of soluble vascular cell adhesion molecule-1 (sVCAM-1) in endothelial cells is reportedly excessive, causing endothelial cell gaps through VE-cadherin and plasma leakage, which is the basic mechanism for shock in dengue hemorrhagic fever (DHF). Objective To determine the association between sVCAM-1 levels and severity of dengue hemorrhagic fever in children. Methods This cross-sectional study was done in children with DHF at Dr. M. Djamil Hospital, Padang, West Sumatera. Subjects were diagnosed according to the 2011 WHO criteria and selected by consecutive sampling. They were grouped as DHF with or without shock. Examination of sVCAM-1 levels was done by ELISA method. Mann-Whitney test with a significance of P<0.05 was used for statistical analysis. Results A total of 66 patients were collected from January 2018 to December 2019, but 2 patients were excluded. The 64 subjects who met the inclusion criteria consisted of 32 (50%) DHF without shock and 32 (50%) DHF with shock. Median sVCAM-1 was significantly higher in the DHF with shock group (840 ng/mL) than in DHF without shock group (598 ng/mL) (P<0.05). Conclusion There was a significant association between higher sVCAM-1 levels and greater severity of dengue hemorrhagic fever in children.